Mapping Knowledge Structure and Themes Trends of Post-operative Rehabilitation of Hip Fractures in the Elderly: A Bibliometrics and Visualization Study - Hu, Liuchao; Wei, Qiushi; Luo, Ziheng; Wang, Bin; Wu, Zhifang; He, Mincong; He, Xiaoming; Luo, Yiwen (Frontiers in Surgery, 2022)
BACKGROUND: Hip fractures are a common type of fracture in the elderly, which is characterized by many complications and high mortality. Many topics concerning postoperative rehabilitation of hip fracture in elderly people still remain controversial, and the global research trend in this field has not been well-studied yet.The aim of the present study was to illustrate the overall knowledge structure, development trends, and research hotspots of postoperative rehabilitation of hip fracture in elderly people.METHODS:Articles and reviews regarding postoperative rehabilitation of hip fracture in elderly people from 2001 to 2021 were identified from the Web of Science database. An online bibliometric platform, CiteSpace, and VOSviewer software were used to generate visualization knowledge maps including annual trends of publications, contributions of countries, institutions, authors, funding agencies and journals, and clustering of keywords.RESULTS: A total of 1724 publications were identified from WoSCC. In the past 20 years, the number of published studies on rehabilitation of hip fracture in the elderly exhibited an overall upward trend. The USA was the leading contributor in this field with the largest publications (354, 20.65%) and the most citations (13786 times). The international cooperation map among relevant countries/regions indicated that the USA collaborated most closely with Canada and China. University maryland and professor Marcantonio ER were the most prolific institution and influential authors, respectively. Injury-International Journal Of The Care Of The Injured was the most productive journal concerning the research of postoperative rehabilitation of hip fracture in elderly people.The keywords co-occurrence analysis identified six clusters:quality of life study, rehabilitation and outcomes study, cognitive impairment study, operative approaches study, mortality study, osteoporosis study.CONCLUSIONS: There will be an increasing number of publications on the research of postoperative rehabilitation of hip fracture in elderly people , and the United States stay ahead in this field. Our findings could offer practical sources for scholars to understand the current status and trend of studies on rehabilitation of hip fracture in the elderly and provide references and suggestions for the development of related researches in the future.